MF/HF帯オーロラ電波の地上・衛星同時観測 - 佐藤, 由佳; 熊本, 篤志; 加藤, 雄人; 新堀, 淳樹; 門倉, 昭; 小川, 泰信; Sato, Yuka; Kumamoto , Atsushi; Katoh , Yuto; Shinbori , Atsuki; Kadokura, Akira; Ogawa, Yasunobu (2015)
第6回極域科学シンポジウム [OS] 宙空圏 11月16日（月） 国立極地研究所１階交流アトリウム conference object